Violations of Linguistic Politeness in The Film Im Westen Nichts Neues (2022) By Erich Maria Remarquse - Nurul Fadilah; Misnah Mannahali; Hasmawati Hasmawati (Phonologie : Journal of Language and Literature, 2026)
Abstract. This study examines violations of linguistic politeness in the film Im Westen Nichts Neues (2022) by Erich Maria Remarque using Brown and Levinson’s politeness theory. The study aims to describe forms of positive and negative face violations and to identify factors contributing to these violations. A qualitative descriptive method was employed, with data consisting of characters’ utterances containing face-threatening acts. Data were collected through observation and note-taking techniques and analyzed using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing. The findings reveal 17 utterances containing politeness violations, consisting of 7 positive face violations and 10 negative face violations. Positive face violations appear in the forms of insults, silencing, rejection of emotions, and disregard for feelings, while negative face violations manifest as direct commands, prohibitions, and threats. The causes of these violations include external factors such as war conditions, rigid military hierarchy, and demands for rapid action, as well as internal factors related to characters’ emotional states, including fear, fatigue, anger, and despair. These findings indicate that politeness violations in the film function as linguistic adaptations to intense social and psychological pressure rather than merely expressions of disrespectKeyword: pragmatics, violations of linguistic politeness, positive face, negative face, Im Westen Nichts Neues